The Rational Use of Human Serum Albumin and its Clinical Outcomes in Hospitalized Hypoalbuminemic Patients - Zida Naswa Febriana; Fitria Wahyuning Wulan; Shofiatul Fajriyah; Ade Giri Ayu Anjani; Lelly Winduhani Astuti; Erni Anika Sari (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Background: Hypoalbuminemia is defined as a serum albumin level <3.5 g/dL, with clinically significant levels <2.5 g/dL associated with increased morbidity and mortality. Human Serum Albumin (HSA) is administered to increase serum albumin levels; however, its use requires evaluation to ensure rational prescribing and optimal therapeutic outcomes. Objective: This study aimed to evaluate the pattern of HSA use, analyze changes in serum albumin levels, and determine the relationship between the rationality of HSA use and albumin level achievement in hospitalized patients with hypoalbuminemia at Bhayangkara Hospital Kediri. Methods: This observational retrospective study used medical records of patients hospitalized from January to December 2025. A total of 32 patients meeting the inclusion criteria were selected using total sampling. Data were analyzed using the Paired t-test and Chi-Square test. Results: Most patients were male (59.37%), aged >60 years (65.63%), and hospitalized for <10 days (78.13%). Among patients receiving 20% HSA therapy, 28 patients (87.50%) received rational therapy, while 4 patients (12.50%) received irrational therapy based on the 2023 National Formulary criteria. Paired t-test analysis showed a significant increase in serum albumin levels after HSA administration (p<0.05). However, Chi-Square analysis showed no significant association between the rationality of HSA use and achievement of albumin level improvement (p>0.05). Conclusion: HSA therapy significantly increased serum albumin levels, although rationality of use was not significantly associated with albumin target achievement